A Rapid and Cost Effective Hardening Method for Tissue Culture Derived Banana Plantlets (Plant Tissue Culture and Biotechnology, 2024)
The present study was aimed to develop a cost effective method for the hardening of tissue culture derived plants of banana var. Robusta. Two approaches were investigated to reduce cost.  First, the shoots inoculated in rooting medium were incubated in (i) growth room under controlled temperature and light conditions for four weeks (RL) (ii) shadehouse exposed to natural light and ambient temperature (RP). The plants obtained from these treatments were given five hardening treatments (a) direct planting in polybags (filled with 1 : 1 Soil and leaf mould) (DP), (b) DP plants covered individually with transparent polybags (DPC), (c) DPC plants placed in tray of water (up to 3 cm height)-DPCW (d) DP plants kept in polytunnel (DPP) (e) DP plants placed in tray of water and kept in polytunnel DPWP, (f) control plants (CN)-primary hardened in potrays kept in polytunnel for four weeks followed by transplantation to polybags (filled with3:1 Soil and leaf mould). RP Plants were greener and sturdier with less hyperhydricity. Rooting outside the lab (RP) reduced the cost as the growth room space during rooting could be saved and so there is saving in electricity of lighting and climate control. 80% of plants in control and 50% plants in direct planting (DP) survived.  In all other treatments 100% survival was observed.  RP-DPCW and RP-DPWP plants showed the best performance in terms of visible appearance and accumulation of biomass.  The method employed could reduce the hardening period from 12 weeks (CN) to 8 weeks.  The cost reduction occurs in this process by a) omitting primary hardening process which requires costly potting media, manpower and climate controlled greenhouse, b) Lab space could be saved as incubation for rooting can be done in shade house thereby saving electricity c) As there is 4 weeks saving in hardening, shade house space could be utilized for hardening more plants. The method could be adopted for hardening in small nurseries to large industries and can result in cost reduction of plantlets. Saving of 4 weeks for hardening will be highly beneficial to the micropropagation industries for delivering plants to farmers in time during peak planting seasons.Plant Tissue Cult. & Biotech. 34(1): 11-24, 2024 (June)